Penggunaan Kunyit Putih (Curcuma zedoaria) Untuk Pengendalian Larva Aedes sp. - Ahliana Ahliana; Isnawati Isnawati; Muhammad Irfa'i (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2019)
Abstract: White Turmeric Larvicides (Curcuma zedoaria) Against Death of Aedes sp. Larvae. Dengue Hemorrhagic Fever is a disease transmitted through mosquito bites from the genus Aedes sp. Chemical control is carried out by killing larvae using abate but can cause resistance from the target organism, to solve this problem by using natural insecticides, namely white turmeric. This study aims to determine the effectiveness of white turmeric larvae (Curcuma zedoaria) on the death of Aedes sp. Larvae. The type of research used is pure experiment. In this study researchers can control the course of the experiment. The sample used was 25 larvae which were put into container boxes with various concentrations and length of contact time. The results of the analysis of concentration variations showed sig 0.05). The duration of contact showed sig